Green Supply Chain Management Strategy and Sustainable Financial Performance: The Moderating Role of Regulatory Pressure and Green Literacy on Export SMES in North Sumatra - Abdelina; Lilis Saryani Lubis; Juwita Handayani; Ahmad Sayuti Pulungan (International Journal of Economics (IJEC), 2026)
This study aims to analyze Green Supply Chain Management (GSCM) strategies in enhancing sustainable financial performance among export SMEs in North Sumatra, examining the moderating roles of regulatory pressure and green literacy. Employing a qualitative approach with a multi-site case study design, this research involved 18 export SMEs from the plantation (palm oil, rubber, coffee), fisheries, and handicraft sectors across Medan, Deli Serdang, and Serdang Bedagai regencies. Data collection was conducted through in-depth interviews, participant observation, and document analysis from March to August 2025. The findings reveal that GSCM implementation contributes positively to sustainable financial performance through operational cost efficiency, expanded export market access, and strengthened reputation among international buyers. Regulatory pressure is proven to strengthen the GSCM-financial performance relationship, while green literacy serves as a catalyst for enhancing the effectiveness of green strategy implementation. This research provides theoretical contributions to the development of GSCM models within the SME context in developing economies, as well as practical implications for policymakers and business actors in formulating sustainability strategies oriented toward long-term financial performance